Enhancing Electronic Partograph Innovation to Boost Midwives’ Ability to Manage Obstetrical Issues in West Pasaman Regency - Larasati, Timmy; Dioso, Regidor III; Hassan, Hafizah Che (PT. Riset Press International, 2025)
Obstetric problems are one of the main challenges in maternal and child health. The high maternal and infant mortality rates in Indonesia indicate the need to improve midwives' skills in handling this problem. One solution that can be implemented is electronic partographs, which are expected to increase the effectiveness and efficiency of monitoring and handling patients. This study aims to evaluate the effect of electronic partograph innovation on midwives' ability to handle obstetric problems in West Pasaman Regency. Quantitative research methods are expected to obtain valid and reliable data regarding improving midwives' abilities and their impact on maternal and infant health outcomes. This study used a quantitative research design with a pre-test and post-test approach. The sample consisted of 120 midwives working in health centers in West Pasaman Regency. Data were collected through a questionnaire piloted before and after the implementation of the electronic partograph. Data analysis used descriptive and inferential statistics to determine the significance of differences in midwives' abilities before and after the intervention. After implementing the electronic partograph, the results showed a significant increase in midwives' abilities to handle obstetric problems. The innovation of the electronic partograph has proven effective in improving the ability of midwives to handle obstetric problems in West Pasaman Regency.